Classification of escherichia coli bacteria by artificial neural networks - Avci, M; Yildirim, W (IEEE, 2002)
Through this paper, four different neural network structure which are multi layer perceptron, radial basis function, general regression neural network and probabilistic neural network were applied to the escherichia coli bacteria benchmark and most efficient neural network architecture for this data has been obtained. Better classification accuracy than the reference work using ad hoc structured probability model was achieved by probabilistic neural network.
Keywords: Back propagation; escherichia coli data; general regression neural network; multi layer perceptron; probabilistic neural network; radial basis function; PROTEIN LOCALIZATION SITES; Automation & Control Systems; Computer Science